Revisiting glucose uptake and metabolism in schistosomes: new molecular insights for improved schistosomiasis therapies - You, Hong; Stephenson, Rachel J.; Gobert, Geoffrey N.; McManus, Donald P. (Frontiers in Genetics, 2014)
A better understanding of the molecular mechanisms required for schistosomes to take up glucose, the major nutritional source exploited by these blood flukes from their mammalian hosts, and the subsequent metabolism required to fuel growth and fecundity, can provide new avenues for developing novel interventions for the control of schistosomiasis. This aspect of parasitism is particularly important to paired adult schistosomes, due to their considerable requirements for the energy needed to produce the extensive numbers of eggs laid daily by the female worm. This review describes recent advances in characterising glucose uptake and metabolism in schistosomes. Potential intervention targets are discussed within the insulin signalling and glycolysis pathways, both of which play critical roles in the carbohydrate and energy requirements of schistosomes.